Identification of strategies for enhancing member commitment in Greek agricultural cooperatives: The opinion of cooperative experts (National Administration Journal, 2021)
In the era of globalization, where competition is growing intensively, the cooperation between small scale farmers can assist them to be sustainable and survive. However, the situation with cooperatives in Greece is found to be on a downward trend due to their poor economic performance, which is later expressed by the diminished commitment of their members. In order to address the described problem we employed a qualitative study consisted of 10 guided interviewees with “cooperative experts”. Through the interviews the participants were asked to clarify their opinions on two major themes: 1) Common Greek cooperative issues, and 2)Suggestions on strategies employed by cooperatives to enhance members’ commitment. Through our analysis we identified the issues related to the poor management of the cooperatives of the past as the major problems of cooperative in Greece. Regarding the strategies for enhancing commitment of members, the majority of participants highlighted the importance of improving the communication and quality of information provided by the coop to its members for building strong bond of trust and ultimately enhancing their commitment. Although, the improvement of communication takes time and requires consistent effort. Hence, cooperatives may act on employing the appropriate experts in order to improve their process of production and marketing. Strengthening the levels of expertise in the economic activities of the cooperative may assist on the satisfaction of members and enhance their commitment to the coop.
Keywords: Member commitment; qualitative analysis; cooperatives